2017
DOI: 10.1109/tpel.2016.2565642
|View full text |Cite
|
Sign up to set email alerts
|

Three-Phase PLLs: A Review of Recent Advances

Abstract: A phase-locked loop (PLL) is a nonlinear negativefeedback control system that synchronizes its output in frequency as well as in phase with its input. PLLs are now widely used for the synchronization of power electronics-based converters and also for monitoring and control purposes in different engineering fields. In recent years, there have been many attempts to design more advanced PLLs for three-phase applications. The aim of this paper is to provide overviews of these attempts, which can be very useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
357
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 648 publications
(359 citation statements)
references
References 118 publications
0
357
0
2
Order By: Relevance
“…Details related to the various modulation techniques used like the Phase-Shifted, Level-Shifted, Space Vector PWM, and Selective harmonic elimination have been discussed in Rodriguez et al 19 Various topologies of multilevel converters and their specific applications and drawbacks have been presented in Leon et al 20 Reviewing the work reported, it can be concluded that the 3-level NPC stands to be a popular configuration owing to its lesser number of devices and capacitors that aids in attaining capacitor voltage balancing which is otherwise difficult in its higher level counterparts. 31 The various PLL structures proposed for single-phase and 3-phase systems and the filtering action of MAF and other filters are broadly discussed in Golestan et al 32,33 and therefore not included in the paper for brevity. The most critical component in a PV system is the power electronic interface and the stresses on its components determine its longevity which in turn is dependent on the working conditions, switch stress, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Details related to the various modulation techniques used like the Phase-Shifted, Level-Shifted, Space Vector PWM, and Selective harmonic elimination have been discussed in Rodriguez et al 19 Various topologies of multilevel converters and their specific applications and drawbacks have been presented in Leon et al 20 Reviewing the work reported, it can be concluded that the 3-level NPC stands to be a popular configuration owing to its lesser number of devices and capacitors that aids in attaining capacitor voltage balancing which is otherwise difficult in its higher level counterparts. 31 The various PLL structures proposed for single-phase and 3-phase systems and the filtering action of MAF and other filters are broadly discussed in Golestan et al 32,33 and therefore not included in the paper for brevity. The most critical component in a PV system is the power electronic interface and the stresses on its components determine its longevity which in turn is dependent on the working conditions, switch stress, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional SRF-PLL has excellent phase tracking capability and dynamic performance under ideal grid conditions. However, when the grid voltage is unbalanced and distorted, an oscillation will be introduced into the phase estimation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the utility grid voltage may be polluted with harmonic components (due to the use of nonlinear loads) or unbalanced conditions (due to single-phase loads) and therefore the utility grid magnitude and frequency may vary between values defined in the grid codes as load conditions change. Phase jumps may also occur and also grid voltage measurements may be incorrect, especially with respect to the DC components, due to the used voltage sensors [6]. The VSI control is required to be fast and accurate under all of these polluted conditions, being the synchronization technique a key feature of the DPG control.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, filters can be implemented by using second-order generalized integrators [9], [10], notch filters [12], complex-coefficient filters [13], [14], lead compensator [15] or moving average filters [16]. When using filtering stages, some aspects must be carefully considered: filters introduce phase delays that must be estimated and compensated in real time [17]; transient response is impaired [6]; filters need to adapt their central frequency during frequency deviations [13] and magnitude and phase jumps affect the estimation of frequency, magnitude and phase [12]. In order to deal with these drawbacks, this paper proposes the use of an sliding method in frequency domain, known as the sliding Goertzel transform (SGT) [18]- [20], to estimate the fundamental and harmonic components of the utility grid.…”
Section: Introductionmentioning
confidence: 99%